STIMULATING THE DEVELOPMENT OF PUBLIC-PRIVATE PARTNERSHIP IN THE FIELD OF SCIENCE AND INNOVATION - G.M. Andreeva; L. Kazbekova; A.B. Dosmailov (Academic Journal of Physical and Chemical Sciences, 2019)
Currently, public-private partnership (PPP) is recognized in Kazakhstan as one of the main instruments for the implementation of economic policy, which is noted in many policy documents. However, the level of use of PPP opportunities in the field of science and innovations remains low due to the unsettled processes of interaction of PPP participants. In this regard, this article examines the issues of the expanded use of PPP in the scientific and innovative sphere in Kazakhstan. The work identified the features of the use of PPP in the science and innovation sphere, outlined its principles, and highlighted the incentives of stakeholders to participate in PPP projects. In addition, on the basis of studying the experience of developed countries, measures have been developed to expand the use of public-private partnership mechanisms in science and innovation in Kazakhstan. Prospective directions for the development of the PPP mechanism for innovation are examined through the prism of the needs and objectives of industrial modernization in the context of the sustainable development of Kazakhstan and the characteristics of the global economy, under which this modernization will be carried out. The main conclusions and proposals formulated in the article can be applied by state bodies in the course of developing state and regional programs supporting scientific and innovative activities. The results of the study can also serve as the basis for more in-depth studies.